Effect of Progressive Muscle Relaxation on Severity of Pain in Patients with Multiple Sclerosis: a Randomized Controlled Trial - Ali Bikmoradi; Azadeh Zafari; Khodayar Oshvandi; Mehrdokht Mazdeh; Ghodratollah Roshanaei (Tehran University of Medical Sciences, 2014)
Background & Aim: Patients with multiple sclerosis suffer from permanent pain. It is being increased to apply relaxation therapy to decrease patientschr('39') pain. The progressive muscle relaxation make the muscles feel more relaxed. The aim of this study was to assess the effect of progressive muscle relaxation on pain among patients with multiple sclerosis .   Methods & Materials: A randomized controlled trial was carried out among 70 patients with multiple sclerosis selected from Hamadan Multiple Sclerosis Society patients. Inclusion criteria involved diagnosed with multiple sclerosis, 20-65 year old patients, having ability to do daily 20-minute exercises, feeling pain, having an EDSS score equal or less than 4.5. Patients were randomly divided into two groups of control and intervention. Patientschr('39') pain was measured using the VAS scale in the two groups at baseline. The relaxation training was implemented among intervention group patients and was repeated three times a week for four weeks. Each session lasted 40 minutes and the patients continued doing exercise at home for the other eight weeks. The control group patients were observed routinely. Patientschr('39') pain was measured eight weeks later in both groups. Data were analyzed using the paired independent t-test in the SPSS-16 .   Results: Muscle relaxation had significant effect on pain among patients with multiple sclerosis (P<0.05). The mean of pain severity decreased from 4.60 ± 1.75 to 3.26±1.88 in the intervention group after the intervention. The mean of pain severity remained constant .   Conclusion: This progressive muscle relaxation can be used for decreasing pain among patients with multiple sclerosis as a non-expensive, safe and simple method .